Antiferrodistortive phase transition in pseudorhombohedral (Pb 0.94Sr0.06)(Zr0.550Ti0.450)O 3 - Solanki, R.S.; Mishra, S.K.; Senyshyn, A.; Ishii, I.; Moriyoshi, C.; Suzuki, T.; Kuroiwa, Y.; Pandey, D. (My University, 2012)
The controversies about the structure of the true ground state of pseudorhombohedral compositions of Pb(ZrxTi1-x)O 3 (PZT) are addressed using a 6% Sr2+ substituted sample with x = 0.550. Sound velocity measurements reveal a phase transition at T c ∼ 279 K. The temperature dependence of full width at half maximum of (h00)pc peaks and the unit cell volume also show anomalies around 279 K even though there is no indication of any change of space group in the synchrotron x-ray powder diffraction (SXRD) patterns. The neutron powder diffraction patterns reveal appearance of superlattice peaks below Tc ∼ 279 K, confirming the existence of an antiferrodistortive phase transition. The Rietveld analysis of the room-temperature and low-temperature SXRD data below Tc shows that the structure corresponds to single monoclinic phase in the Cm space group while the analysis of neutron powder diffraction data reveals that the structure of the ground-state phase below Tc corresponds to the Cc space group. Our analysis shows that the structural models for the ground-state phase based on the R3c space group with or without the coexistence of the room-temperature monoclinic phase in the Cm space group can be rejected.
A combined synchrotron x-ray and neutron powder diffraction study
Keywords: pseudorhombohedral; Pb(ZrxTi1-x)O 3 (PZT); synchrotron